Plant regeneration of Dimocarpus scandens (Winit & Kerr) Boonsuk & Chantar. (Lamyai-Thao) by tissue culture technique - Jitwetkul, A.; Poeaim, A.; Pongtongkam, P.; Chareonsap, P. P.; Poeaim, S. (My University, 2025)
The minimum contamination percentage (25%) was recorded in the experiment using 0.2% mercuric chloride (HgCl2) for 20 min, which was observed to be a 50% germination rate after 2 weeks of culture. The maximum germination rate (68%) was obtained on Murashige and Skoog (MS) solid medium supplemented with 1.0 mg/L 6-benzylaminopurine (BAP), giving a shoot length of 48.00 mm. and root length of 31.40 mm. The optimal condition of nodal segment sterilization was recorded in the experiment using 0.1% HgCl2 for 10 min, which gave 80% survival explants. For shoot induction, it was worked on MS solid medium with 0.5 mg/L 6-benzylaminopurine (BAP) that induced the highest average length of 11.31 mm. The highest root formation frequency (50%) and root length (3.0 mm) were achieved on an MS medium containing 2.0 mg/L indole-3-butyric acid (IBA). The plantlets were acclimatized and established in the soil.
Keywords: Dimocarpus scandens; Plant induction; Seed germination